An exploration of the youths perception toward social entrepreneurship development: Evidence from Bangladesh - Dewan Mehrab Ashrafi; Md Atiqur Rahman Sarker; Junaidah Binti Hashim; Ahasanul Haque; Fatima Kanis Nayan (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2020)
A plethora of researchers has dominantly kept their focal point on the concept of social entrepreneurship and its economic development and sustainable aspect, but very few studies have been carried out which solely emphasized the youth and social entrepreneurship in Bangladesh. This study aims to explore the factors associated with the perception development of social entrepreneurship intention among business school graduates in Bangladesh. Primary data has been collected by using a structured questionnaire on 350 respondents and analyzed by using Spearman correlation. This study revealed most of the young graduates chose to participate in social entrepreneurship since it allows them to be independent and help to fulfill their social spirit. They also perceived that social entrepreneurship as a respectable and noble career. Interestingly, they also considered that job as risky and seems like take the advantage of other difficulties or poverty. They are also do not get family support to do social business because they perceived that social entrepreneurship is only for people who cannot get the desired job.